Beyond innovation. Towards an extended framework for analysing technology policy - Knut Holtan Sørensen (Nordic Journal of Science and Technology Studies, 2016)
This paper analyses technology policy as a scholarly concern and political practice that needs to be taken beyond the present somewhat singular focus on innovation and deployment. We also need to include an interest in the making of infrastructure, the provision of regulations, and democratic engagement. Consequently, this paper introduces the concepts of socialisation and domestication to overcome the instrumental, economic framing of technology policy. These concepts highlight the importance of embedding and enacting new technology. The suggested conceptual framework is used in a brief synthetic analysis of four examples of technology policy and technological development in the Norwegian context: cars, wind power, hydrogen for transport, and carbon capture and storage (CCS).